Anthropometry, physical activity, and the risk of pancreatic cancer in the European prospective investigation into cancer and nutrition. - Berrington de González, A; Spencer, E; Bueno-de-Mesquita, H; Roddam, A; Stolzenberg-Solomon, R; Halkjaer, J; Tjønneland, A; Overvad, K; Clavel-Chapelon, F; Boutron-Ruault, M; Boeing, H; Pischon, T; et al. (2006)
Tobacco smoking is the only established risk factor for pancreatic cancer. Results from several epidemiologic studies have suggested that increased body mass index and/or lack of physical activity may be associated with an increased risk of this disease. We examined the relationship between anthropometry and physical activity recorded at baseline and the risk of pancreatic cancer in the European Prospective Investigation into Cancer and Nutrition (n = 438,405 males and females age 19-84 years and followed for a total of 2,826,070 person-years). Relative risks (RR) were calculated using Cox proportional hazards models stratified by age, sex, and country and adjusted for smoking and self-reported diabetes and, where appropriate, height. In total, there were 324 incident cases of pancreatic cancer diagnosed in the cohort over an average of 6 years of follow-up. There was evidence that the RR of pancreatic cancer was associated with increased height [RR, 1.74; 95% confidence interval (95% CI), 1.20-2.52] for highest quartile compared with lowest quartile (P(trend) = 0.001). However, this trend was primarily due to a low risk in the lowest quartile, as when this group was excluded, the trend was no longer statistically significant (P = 0.27). A larger waist-to-hip ratio and waist circumference were both associated with an increased risk of developing the disease (RR per 0.1, 1.24; 95% CI, 1.04-1.48; P(trend) = 0.02 and RR per 10 cm, 1.13; 95% CI, 1.01-1.26; P(trend) = 0.03, respectively). There was a nonsignificant increased risk of pancreatic cancer with increasing body mass index (RR, 1.09; 95% CI, 0.95-1.24 per 5 kg/m(2)), and a nonsignificant decreased risk with total physical activity (RR, 0.82; 95% CI, 0.50-1.35 for most active versus inactive). Future studies should consider including measurements of waist and hip circumference, to further investigate the relationship between central adiposity and the risk of pancreatic cancer.